2015
DOI: 10.3892/ol.2015.3918
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells enhance the expression of melanoma-associated antigen A4 in a Lewis lung cancer murine model

Abstract: Abstract. The cancer-testis (CT) family of antigens are expressed in multiple types of malignant neoplasm and are silent in normal tissues, apart from the testis. Immunotherapy targeting CT antigens is a promising therapeutic strategy for treatment of solid tumors. One member of this family, melanoma-associated antigen A4 (MAGE-A4), has been demonstrated to be expressed in melanomas and lung cancer. Patients with tumors expressing the MAGE-A4 antigen exhibit specific cellular and humoral immune responses to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(38 reference statements)
1
9
1
Order By: Relevance
“…It has been reported that MDSCs supernatant could upregulate another cancer-testis antigen (CTA), MAGE-A4, in lung cancer (34). In accordance with previous studies, we found that MDSC supernatants could significantly upregulate MAEL, activate EMT, and upregulate stemness-associated genes in esophageal cancer cell lines (Fig.…”
Section: Pmn-mdscs Secreted Tgfb To Upregulate Mael Through Activatinsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that MDSCs supernatant could upregulate another cancer-testis antigen (CTA), MAGE-A4, in lung cancer (34). In accordance with previous studies, we found that MDSC supernatants could significantly upregulate MAEL, activate EMT, and upregulate stemness-associated genes in esophageal cancer cell lines (Fig.…”
Section: Pmn-mdscs Secreted Tgfb To Upregulate Mael Through Activatinsupporting
confidence: 91%
“…Shi and colleagues demonstrated that MAGE-A4, a CTA, could be regulated by MDSC supernatants (34), and Sampson and colleagues demonstrated TGFb could upregulate another Figure 6. MAEL could activate the Akt1/RelA signaling pathway to upregulate IL8.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, numerous recent studies that examine the immunomodulatory role of MDSCs were actually describing immunosuppressive neutrophils. In such studies, authors are often content with using phenotypical evaluation of surface CD11b and/or Ly6G expression, whereas missing, at least in part, the characterization of the suppressive activities of these cells [34][35][36]. Moreover, neutrophil-depletion procedures using anti-Gr1 or anti-Ly6G antibodies are repeatedly presented as MDSC-depleting therapy [37,38].…”
Section: Neutrophils Versus Mdscmentioning
confidence: 99%
“…The name of MDSCs firstly comes from the ability to suppress immune cells via cell‐to‐cell interactions as well as soluble mediators, which have been demonstrated in tumour‐bearing mice models both in vivo and in vitro ; furthermore, in cancer patients, MDSCs were accumulated because myelopoiesis is perturbed instead of generating immunogenic myeloid cells such as dendritic cells, inflammatory macrophages and granulocytes . These cells are distributed systemically, resulting in general immunosuppression.…”
Section: Suppressive Activity Of Mdscsmentioning
confidence: 99%